2021
DOI: 10.3390/app112210593
|View full text |Cite
|
Sign up to set email alerts
|

Multiclass Skin Cancer Classification Using Ensemble of Fine-Tuned Deep Learning Models

Abstract: Skin cancer is a widespread disease associated with eight diagnostic classes. The diagnosis of multiple types of skin cancer is a challenging task for dermatologists due to the similarity of skin cancer classes in phenotype. The average accuracy of multiclass skin cancer diagnosis is 62% to 80%. Therefore, the classification of skin cancer using machine learning can be beneficial in the diagnosis and treatment of the patients. Several researchers developed skin cancer classification models for binary class but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 56 publications
0
12
1
Order By: Relevance
“…It is known from the literature that the accuracy of classi cation declines with the number of classes. The accuracy of the earlier studies reported in [12,13,14,15] is lower than that of the ensemble models that have been suggested. With minimal pre-processing, our ensemble models have outperformed contemporary deep learning-based models as well as dermatologists in the multiclass classi cation of skin cancer.…”
Section: Classi Cation Reportcontrasting
confidence: 66%
See 1 more Smart Citation
“…It is known from the literature that the accuracy of classi cation declines with the number of classes. The accuracy of the earlier studies reported in [12,13,14,15] is lower than that of the ensemble models that have been suggested. With minimal pre-processing, our ensemble models have outperformed contemporary deep learning-based models as well as dermatologists in the multiclass classi cation of skin cancer.…”
Section: Classi Cation Reportcontrasting
confidence: 66%
“…The proposed ensemble model's performance is compared to the most recent deep learning-based models proposed in [12,13,14,15] in Figures 12,15,and 18. The accuracy of the majority voting, weighted averaging, and weighted majority ensemble models is seen to be substantially greater than that of the models provided in [12,13,14,15]. It is known from the literature that the accuracy of classi cation declines with the number of classes.…”
Section: Classi Cation Reportmentioning
confidence: 99%
“…The recent ensemble model in [30,31] achieved accuracy higher than the proposed ensemble models because they ensemble more CNN models that is lead to complexity in the process and used an extra dataset. The recent ensemble model in [33] achieved accuracy higher than the proposed ensemble models because they implemented their experiments on part of dataset by selecting randomly images from each class. The recent ensemble model in [34] achieved accuracy higher than the proposed ensemble models because they ensemble five models to diagnose seven classes of skin lesions types by only using seven classes from ISIC 2019 like HAM dataset and the classification accuracy decrease when the number of diagnostic classes increases.…”
Section: Resultsmentioning
confidence: 97%
“…Table IV shows the comparison between the proposed ensemble models and the recent ensemble models in [29,30,31,32,33,34,35] Although the recent ensemble models used the normal ensemble algorithms but some of them achieved higher accuracy than proposed ensemble learning model because using extra dataset and ensemble with more classification deep learner models lead to increasing the accuracy result. The recent ensemble model in [30,31] achieved accuracy higher than the proposed ensemble models because they ensemble more CNN models that is lead to complexity in the process and used an extra dataset.…”
Section: Resultsmentioning
confidence: 99%
“…With the help of this technique, they claim that their model accuracy was enhanced from 66% to 92%. In another study Kausar et al [34] used some fine-tuning techniques to improve state-of-art deep learning image classification models. They achieved an accuracy of 72%, 91%, 91.4%, 91.7%, and 91.8% for ResNet, InceptionV3, DenseNet, InceptionResNetV2, and VGG-19, respectively.…”
Section: Introductionmentioning
confidence: 99%